A Short and Efficient Approach for the Total Synthesis of (S)‐Zearalenone and (R)‐De‐O‐methyllasiodiplodin by Using Stille and RCM Protocols. Issue 9 (23rd February 2016) - Kumar Dey, Sujit; Ataur Rahman, Mohammad; Alkhazim Alghamdi, Ahmad; Reddy, Basi V. Subba; Yadav, Jhillu S.
Abstract: A concise, flexible, and linear approach has been devised for the total synthesis of the resorcinylic acid lactones ( S )‐zearalenone (2 ) and ( R )‐de‐ O ‐methyllasiodiplodin (4 ) by using a Stille cross‐coupling strategy. The other key steps of the synthesis include a ring‐closing metathesis (RCM), a chemoselective reduction of an α, β‐unsaturated ketone, and a transesterification reaction. Abstract : A concise, flexible, and linear approach has been devised for the total synthesis of the resorcinylic acid lactones ( S )‐zearalenone (2 ) and ( R )‐de‐ O ‐methyllasiodiplodin (4 ) by using a Stille cross‐coupling strategy. The other key steps of the synthesis include a ring‐closing metathesis (RCM), a chemoselective reduction of an α, β‐unsaturated ketone, and a transesterification reaction.